Penerapan Usaha Budidaya Arwana Brazil (Osteoglossum bicirhossum) Bagi Siswa SMKN 1 Sungai Raya Kubu Raya - Setiawan, Agus; Mudlofar, Farid; Sarmila, Sarmila; Shilman, M. Idham; Susilawati, Susilawati; Warastuti, Sri; Putri, Hylda Khairah; Nurfahma, Nurfahma; Kusumawati, Dewi (Politeknik Negeri Pontianak, 2023)
Brazilian Arowana fish is one of the ornamental fish with high economic value that has the potential to be developed in Kubu Raya district. This fish is relatively easy to care for, but there are still many people who are not brave enough to maintain it due to a lack of knowledge. For this reason, it is necessary to adopt technology through PPM activities by utilizing collaboration with SMKs as well as upgrading the competencies that students currently have. With this activity can be an alternative to improve the community's economy. The purpose of this PPM activity is to improve the competence and abilities of students in applying environmentally friendly, efficient and effective Brazilian Arwana ornamental fish farming business technology in a sustainable manner and it is hoped that it can become an example for the surrounding ornamental fish cultivating community. The maintenance process for Brazilian Arowana during PPM activities went well. The time required for one maintenance cycle is 2 months. The containers used consist of 2 types, namely a tarpaulin tub as a container and an aquarium as a container for further maintenance. As many as 420 seeds were sown and given feed in the form of frozen worms and small shrimp. The SR level is 100% so that the harvest can be sold entirely with a profit of Rp. 5,130,000.- and the R/C ratio is 1.54. This PPM activity is expected to spur the community in developing Brazilian Arowana fish farming by applying appropriate technology that is applicable to increase the productivity of aquaculture products in a sustainable and environmentally friendly manner which will ultimately increase the economic level of the community.